The Use of Word Cards on Early Childhood Cognitive - Muliana, Andi; Wahira, Wahira; Asrifan, Andi; Herliin, Herlina (PT. Riset Press International, 2026)
Word card media plays an important role in helping early childhood recognize letter and word symbols gradually. In the early stages, children can learn to recognize the shape of the letters through the cards, and then associate them with the appropriate sounds. In this way, the word card becomes a bridge between the child's speaking ability and the ability to read at the beginning. This study aims to determine the influence of word card use on early childhood cognitive development and analyze the factors that affect the relationship between cognitive development and word card use in early childhood. This research method uses a quantitative approach with an experimental method. The data collection technique in this study was carried out through tests and observations. The data analysis technique in this study uses the latest version of SPSS statistical software to analyze the relationship between cognitive variables and the use of word card media in early childhood. The implementation of word card media by teachers has been running effectively and systematically. There was a positive and significant influence between the use of word card media on children's cognitive abilities, which was shown by a strong correlation coefficient.